The Influence of The Madrasah Aliyah Principal's Leadership Style, Reward System, and Teacher Competition Intensity On The Effectiveness of Madrasah Aliyah In Private Madrasah Aliyah In The Riau Islands Province - Achmad Fauzi; Risnita Risnita; Jamaluddin Jamaluddin (Dinasti International Journal of Education Management And Social Science, 2024)
The research was conducted at a private Madrasah Aliyah School in the Riau Islands, where the research sample area used area or regional sampling techniques. The Riau Islands Province consists of several cities or districts so it was taken based on the map, namely the West, Central and East regions. Representing the Western region is Karimun Regency, the Eastern region is represented by Tanjungpinang City, the Central region is represented by Batam City. With a total of 91 respondents, 30 were used as trial samples, and the remaining 61 as research samples. The research variables were: Influence of Leadership Style (X1), Reward System (X2), Teacher Competition Intensity (X3) and Madrasah Effectiveness (X4). This research aims to determine the extent of the influence of the Leadership Style of Madrasah Heads, the Reward System and the Intensity of Teacher Competition on the Effectiveness of Madrasah Aliyah in Private Madrasah Aliyah, Riau Islands Province. This research uses a quantitative approach with a survey method. Data were analyzed using simple and multiple correlation and regression techniques. The results of this research show that the leadership style, reward system and intensity of teacher competition have a joint influence on the Madrasah Aliyah effectiveness variable of 92.8%, which means it is very strong. So it can be concluded that the better the leadership style, reward system and intensity of teacher competition, the better the effectiveness of Madrasah Aliyah.